Semen quality and frozen semen production in Pasundan bulls: A molecular weight perspective on seminal plasma and spermatozoa protein (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: To determine the correlation between the molecular weight (MW) of proteins in seminal plasma and spermatozoa and the quality of fresh and frozen semen production in Pasundan bulls. Materials and methods: Nine selected Pasundan bulls, aged 5–10 years, from the Regional Artificial Insemination Center at Ciamis, West Java, Indonesia, were used in the study, with fresh semen sperm motility ≥70% and